Music Therapy and Intersectionalities: Critical Perspectives on Structural Dynamics of Violence and Oppression and How to Confront them Through Emancipatory Practices in Brazilian Music Therapy - Ribeiro, Wagner Junio; Ribeiro, Luiz Paulo; Magalhães Rosário, Verônica (Voices: A World Forum for Music Therapy, 2025)
This paper reflects on the urgency of incorporating intersectional perspectives into music therapy practice, emphasizing the need for an intersectional approach that includes anti-racist, feminist, and LGBTQIA+ (queer) perspectives in order to transform healthcare and combat possible institutional violence. Based on a critical review of the literature, it offers reflections that point to the need for music therapy to expand its dimensions in order to integrate decolonial knowledge and anti-oppressive practices, recognizing the complex interaction between race, gender, and sexuality. The analysis reveals that historical structures of oppression, such as racism, sexism, and LGBTQIA+phobia, perpetuate inequalities and restrict access to quality health services.As a result, the text highlights the need to rethink music therapy training curricula, promoting critical awareness and the valorization of multicultural knowledge based on multiple epistemes. By proposing a music therapy practice committed to social justice, the study calls on professionals, educators, and managers to critically rethink their approaches, expanding spaces for listening, inclusion, and transformation, and thus contributing to the promotion of comprehensive and emancipatory health, capable of addressing the multiple dimensions of contemporary violence. Editorial Comment How complex music therapy is when we experience it at the intersection of race, gender, and sexuality! The authors have a deep understanding of this kind of intersectionality and generously invite us to explore this territory. They themselves acknowledge the work of many colleagues in Brazil who are working to confront the violence generated by colonialism in terms of inequality, injustice, and violence.